STUDY OF HEAT TRANSFER AND PHASE BEHAVIOUR OF MLXED REFRIGERANT IN MAIN CRYOGENIC HEAT EXCHANGER TOWARDS MAXIMIZE LNG PRODUCTION - ZAINAL ABIDIN, MOHD ZAKI (2013)
Liquefied Natural Gas (LNG) industry has shown a significant increase in its production due its benefit as a reliable source of energy. Increasing LNG production means more energy is required especially for liquefaction plant. This is due to the lack of efficiency contributed by its equipments especially by Main Cryogenic Heat Exchanger (MCHE). In order to improve the efficiency, Mixed Refrigerant (MR) is used in MCHE as the refrigerant. However, each component in MR has a significant contribution on the mixture behavior and phase changing trend occurring in MCHE, with proprietary issue of the internal structure of MCHE. In this study, heat transfer and phase behavior of MR on the shell side of MCHE are investigated.